CHARACTERISTICS OF ROOT CANAL MICROBIOTA IN ACUTE PULPITIS OF TEMPORARY TEETH - O.V. Klitynska; T.I. Zorivchak; R.Y. Krychak (Український стоматологічний альманах)
Aims. To determine the representatives of the microbiota of the root canals seeded in acute forms of pulpitis of temporary teeth among children of the Transcarpathian region, taking into account the endemic features of the Transcarpathian region and its influence on the course of the carious process.